2006
DOI: 10.1308/003588406x117115
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Management of Acute Traumatic First-Time Anterior Shoulder Dislocation Among Trauma Clinicians in the UK

Abstract: INTRODUCTION The aim of this work was to survey how acute traumatic first-time anterior shoulder dislocation (AFSD) is managed among trauma clinicians in UK using a postal questionnaire.PATIENTS AND METHODS A total of 150 questionnaires were sent out to active consultant members of the British Trauma Society in the UK. Questions were laid out in two 'workgroups'. In Workgroup One, an assortment of questions was included regarding choices and methods of analgesia, methods of monitoring used, methods of reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…30 They reported that a standard management protocol is still not present and there are no standard guidelines for the management of anterior shoulder dislocation. Of the 90 clinicians involved in the study (orthopaedic surgeons, accident and emergency consultants and consultant anaesthetists) only 22 said they used a local protocol.…”
Section: Current Practicementioning
confidence: 99%
“…30 They reported that a standard management protocol is still not present and there are no standard guidelines for the management of anterior shoulder dislocation. Of the 90 clinicians involved in the study (orthopaedic surgeons, accident and emergency consultants and consultant anaesthetists) only 22 said they used a local protocol.…”
Section: Current Practicementioning
confidence: 99%
“…Die Rückläuferquote von 51,8 % aus deutschen Krankenhaus-bzw. Belegabteilungen entspricht den Ergebnissen anderer vergleichbarer Umfragen[13,14] und der von uns im Jahr 2005 durchgeführten Erhebung, auch wenn eine stärkere Beteiligung wünschenswert gewesen wäre. Die Zusammensetzung der ausgewählten Abteilungen nach Fachrichtung als auch deren Verteilung über das Bundesgebiet entspricht der befragten Gesamtheit.…”
unclassified
“…Non-operative post-reduction management has been the main stay of UK orthopaedic surgeons over the years (Freudmann and Hay, 2004;Chong et al, 2006). However, the literature shows a mixed picture of results with no cohesive protocol seeming to make any difference in terms of reducing recurrence rates of dislocation (Paterson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide-ranging opinion in the literature about what constitutes ideal post-reduction management, but as usual, the options of non-operative versus operative management have sparked an ongoing debate. In a recent survey, most UK orthopaedic surgeons prefer to treat acute shoulder dislocations non-operatively in a sling in internal rotation (Chong et al, 2006). However, the risk of recurrent shoulder dislocation and ongoing instability in young patients is high, ranging from 47% to 100% in some studies (Rowe, 1956;Henry and Genung, 1982;Hovelius et al, 1983;Wheeler et al, 1989;Hoelen et al, 1990;Marans et al, 1992;Vermeiren et al, 1993;Arciero et al, 1994;Hovelius et al, 1996).…”
Section: Introductionmentioning
confidence: 99%